Response of maize phenology and grain yield to various nitrogen rates and plant spacing at Bako, West Ethiopia - Begizew Golla; Desalegn Chalchisa (Open Journal of Plant Science - Peertechz Publications, 2019)
Maize hybrid responds differently to various N rates and plant spacing with changing in grain yield and phenological period to reflect the respond. A field experiment was conducted at Bako research farm in the year 2017 to determine the response of maize phenology and grain yield for various nitrogen fertilizer rates and plan spacing. The experiment was arranged in a Randomized Complete Block Design in factorial combination with three replications. Three plant spacing i.e. 20cm, 30cm and 40cm, with one row spacing of 75cm and six nitrogen rates i.e. 0kg ha-1, 23kg ha-1, 46kg ha-1, 69kg ha-1, 92kg ha-1 and 115kg ha-1 were assigned to the experimental plot by factorial combinations. The results showed that reduction in plant spacing and nitrogen starvation resulted delaying to attain 50% tasseling and silking while it speeding up maturity period. Maximum grain yield (10,207.8 kilo gram per hectare) obtained under the narrowest plant spacing (20 centimeters) with application of the highest rate of nitrogen (115 kilo gram nitrogen per hectare). This yield result surpassed by 8.9% compared to the standard check. The experiment indicated an increasing trend of grain yield with increasing N rate and decreasing plant spacing, so further increasing of N rates and reducing plant spacing might further increased the grain yield.